Modelo ProLab: Earhart Travel, plataforma digital que promueve el turismo seguro para mujeres - Gómez Díaz, María Cristina (2024)
In a context where more women are choosing to undertake independent travel, either alone or in all-female groups, there has been a growing increase in concerns about the safety of female tourists. In the Peruvian context, this country frequently appears on lists of dangerous tourist destinations for women, which has raised additional concerns about safety. In this scenario, Earhart Travel seeks to address two key social issues. Firstly, the company focuses on the growing concern about the safety of women travelling alone or in all-female groups; secondly, it seeks to empower women in the Peruvian tourism industry, where lack of gender equity and limited representation in leadership roles are relevant concerns. To address these issues, Earhart Travel has developed a value proposition focused on ensuring safe, authentic, and empowering tourist experiences for women who wish to travel independently within Peru. To do so, Earhart Travel will provide a service focused on safety, empowerment, and authenticity. The company seeks to transform the way women experience tourism by offering safe and enriching travel experiences specially designed for them. The initial investment of 956,880 Soles reflects the amount needed to start the company. However, the highlight is the Net Present Value (NPV) of 9 ́278,247.29 Soles, which shows that the project has a positive net value, implying that it will be profitable and generate a positive return on investment. In addition, the Internal Rate of Return (IRR) of 289.45% significantly exceeds the Weighted Discount Rate of Capital Cost (WACC) of 30.638% , indicating that the project is not only financially viable, but also presents an attractive return compared to the cost of capital. These financial indicators support the strength of Earhart Travel's business model and its ability to generate sustainable profits in the market. In terms of social sustainability, Earhart Travel closely aligns with the United Nations Sustainable Development Goals (SDGs), specifically SDG 5 (Gender Equality) and SDG 8 (Decent Work and Economic Growth). The company seeks to empower women and promote vii inclusive and sustainable economic growth, while also contributing to improving the perception of safety for female tourists in Peru.